1984
DOI: 10.3382/ps.0631764
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrient Density on Growth and Carcass Composition of Weight-Segregated Leghorn Pullets

Abstract: Leghorn pullets were weight-segregated at either 8, 12, or 16 weeks of age and classified as either light, medium, or heavy weight. Six replicate cages each containing 10 birds of each of the three weight groups received a control diet ad libitum that contained 15% CP and provided 2800 kcal ME/kg. The same replicate number of light-weight pullets were also offered either high protein (18% CP, 2800 kcal ME/kg) or low energy (15% CP, 2400 kcal ME/kg) diets. Groups of heavy pullets received either low protein (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…With pullets identified as being small at 12 wk of age, these same authors show little differential response of birds to diets of 3,100 kcal ME/kg and 20% CP vs. diets of 2,700 kcal/kg and 14% CP. The above results are similar to those reported by Leeson and Summers (1984b), where genetically small pullets in a population failed to respond to dietary manipulation. Another factor that may confound experiments involved with the use of high energy diets is inadequacy of protein or amino acid intake.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With pullets identified as being small at 12 wk of age, these same authors show little differential response of birds to diets of 3,100 kcal ME/kg and 20% CP vs. diets of 2,700 kcal/kg and 14% CP. The above results are similar to those reported by Leeson and Summers (1984b), where genetically small pullets in a population failed to respond to dietary manipulation. Another factor that may confound experiments involved with the use of high energy diets is inadequacy of protein or amino acid intake.…”
Section: Discussionsupporting
confidence: 93%
“…Feed intake per cage group was also ascertained over these time periods. Shank length was measured when birds were 28, 36, and 84 days of age (Leeson and Summers, 1984b).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary energy dynamics in animals are complex depending on the dietary nutrients provided, and several reviews have shown their complexity in depth [20][21][22]. Ultimately, changes in dietary energy can enhance or reduce pullet growth rate and modify the growth of fat tissue, muscles and the relationship between fat and lean deposition [23,24].…”
Section: Introductionmentioning
confidence: 99%